On the language ecology of German in Denmark - Geyer, Klaus (Kalbotyra, 2024)
This article analyses the German language in Denmark in its various contexts of language ecology. A crucial aspect of this approach is that German is not only considered, for example, as an intensely taught and learned foreign language in the education system or as the vivid language of the German minority in the south of Jutland, but that all those areas in which the German language plays a role in the Danish society are dealt with, thus including the enormous importance of German in Danish tourism and in business and economic life in general. In this way, a systemic overview over the language ecology of German in Denmark can be reconstructed.For a better understanding of today’s situation of German in Denmark, a brief historical outline of the centuries of intensive language contact between German and Danish is provided at the end of the article.
Keywords: language ecology; German in Denmark; education system; tourism; economy; German minority